2023
DOI: 10.3390/nano13060958
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II) Complex Grafted Ti3C2Tx MXene Nano Sheet with Photothermal/Photodynamic Synergistic Antibacterial Activity

Abstract: For a long time, the emergence of microbial drug resistance due to the abuse of antibiotics has greatly reduced the therapeutic effect of many existing antibiotics. This makes the development of new antimicrobial materials urgent. Light-assisted antimicrobial therapy is an alternative to antibiotic therapy due to its high antimicrobial efficiency and non-resistance. Here, we develop a nanocomposite material (Ru@MXene) which is based on Ru(bpy)(dcb)2+ connected to MXene nanosheets by ester bonding as a photothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The production of 1 O 2 in the MXene group was detected under near-infrared light irradiation with 1,3diphenylisobenzofuran (DPBF), and the production of 1 O 2 was attributed to the energy transfer of photoexcited electrons to triplet oxygen ( 3 O 2 ) from Ti 3 C 2 T x as well as the LSPR effect of metal nanoparticles (Han et al, 2018a;Zhang et al, 2019). Another study also confirmed that after irradiation with a 532 nm laser (20 mW) for 30 min, the MXene group showed a decrease in absorbance at 417 nm, which produced a single linear state of oxygen (Liu et al, 2023a). MXene produces a large amount of ROS from the material's PDT under near-infrared light irradiation, while the material's superior PTT raises the ambient temperature of Frontiers in Bioengineering and Biotechnology frontiersin.org the bacteria.…”
Section: Induced Generation Of Oxidative Stressmentioning
confidence: 79%
“…The production of 1 O 2 in the MXene group was detected under near-infrared light irradiation with 1,3diphenylisobenzofuran (DPBF), and the production of 1 O 2 was attributed to the energy transfer of photoexcited electrons to triplet oxygen ( 3 O 2 ) from Ti 3 C 2 T x as well as the LSPR effect of metal nanoparticles (Han et al, 2018a;Zhang et al, 2019). Another study also confirmed that after irradiation with a 532 nm laser (20 mW) for 30 min, the MXene group showed a decrease in absorbance at 417 nm, which produced a single linear state of oxygen (Liu et al, 2023a). MXene produces a large amount of ROS from the material's PDT under near-infrared light irradiation, while the material's superior PTT raises the ambient temperature of Frontiers in Bioengineering and Biotechnology frontiersin.org the bacteria.…”
Section: Induced Generation Of Oxidative Stressmentioning
confidence: 79%
“…Loading ICG onto Ti 3 C 2 T x nanosheets combines the photothermal effect of Ti 3 C 2 T x with the photodynamic effect of ICG, resulting in a 100% increase in the vitality loss of S. aureus under NIR light spectrum [ 109 ]. Ti 3 C 2 T x nanocomposites based on Ru(II) complex grafting achieve almost 100% bactericidal activity against E. coli (200 μg/mL) and S. aureus (100 μg/mL) upon exposure to a xenon lamp [ 110 ] ( Figure 6 ). ZnTCPP-modified Ti 3 C 2 T x captures bacteria via surface electrostatic interactions [ 111 ].…”
Section: Classification Of the Ti 3 C 2 ...mentioning
confidence: 99%
“… Ti 3 C 2 T x /photosensitizer composite material [ 110 ]. ( A ) A sSchematic illustration of the preparation of Ru@MXene nanocomposites.…”
Section: Figurementioning
confidence: 99%
“…ZnO-NMts find applications in various everyday products including catalysts, environmental remediation, personal care products, cosmetics, vaccine adjuvants, and antibacterial ointments. [1][2][3] Ferreira and Liu et al [4,5] have discovered that nanomaterials of small size can be an optimal option for the antibacterial process. Given that bacteria can be transmitted through a damp mask, enhancing the mask's antibacterial capability is crucial to prevent cross-infection or secondary infection during usage.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] Ferreira and Liu et al. [ 4,5 ] have discovered that nanomaterials of small size can be an optimal option for the antibacterial process. Given that bacteria can be transmitted through a damp mask, enhancing the mask's antibacterial capability is crucial to prevent cross‐infection or secondary infection during usage.…”
Section: Introductionmentioning
confidence: 99%